Motivation and strategies in acquiring the French language among undergraduates in Universiti Putra Malaysia - Abdul Halim, Hazlina; Abd Rahim, Normaliza; Mansor, Nor Shahila (Persatuan Linguistik Malaysia, 2017)
This research examined the motivation of Universiti Putra Malaysia (UPM)’s undergraduates in learning French language. Hence, the objectives of this research were to find out the factors contributing to the motivation and strategies employed by the learners to increase their motivation. The study also administered Schmidt & Watanabe (2001) questionnaire to 100 respondents for the quantitative inputs. In addition to the questionnaires, interview sessions were conducted with the selected respondents by adapting Gardner’s (2006) Socio-educational Theory and Gagné and Deci (2005)’s Self-determination theory. Ten third-year students majoring in French in UPM were selected for the interview. Each interview took about 30 minutes. The results showed that the factors including the lecturer’s role, course line, learning environment, peers, examination results, future needs or jobs and self-interest could influence the undergraduates’ motivation. Moreover, the results found that the strategies that can be used to increase the undergraduates’ motivation are the improvement of teaching quality, increasing the autonomous motivation of undergraduates and peers learning. However, the lecturers’ role was determined as the most significant effect on the undergraduates’ motivation in acquiring a foreign language.